Metabolic syndrome in adults with a history of juvenile arthritis - Sule S (Dove Medical Press, 2018)
Sangeeta Sule,1 Kevin Fontaine2 1Department of Pediatric, Pediatric Rheumatology, Johns Hopkins University, Baltimore, MD, USA; 2Department of Health Behavior, University of Alabama at Birmingham, Birmingham, AL, USA Objective: The objective of this study was to determine the risk of obesity and metabolic syndrome in adults with a history of juvenile arthritis (JA). Methods: Using the National Health and Nutrition Examination Survey (NHANES), we compared the characteristics of respondents with arthritis (JA vs rheumatoid arthritis [RA]) to those of the control group without arthritis. We used logistic regression analyses, controlling for age, race, and gender, to determine the ORs for metabolic syndrome. Results: Obesity was increased in the JA group with 67% respondents having body mass index ≥30 kg/m2 vs 55% respondents in the no arthritis cohort (p=0.004). In unadjusted analyses, there was increased odds of metabolic syndrome in JA (OR 6.2, p=0.001) and RA groups compared to those without arthritis (OR 7.7, p=0.001). After adjusting for age, gender, and race, the odds of metabolic syndrome remained increased in JA (OR 5.2, p=0.001) and RA (OR 3.2, p=0.001) groups. Conclusion: Adults with a history of JA have a significantly increased risk of metabolic syndrome compared to those without arthritis. These findings are important because metabolic syndrome has been associated with an increased risk of cardiovascular disease and death in other populations. Keywords: juvenile arthritis, outcomes research, cardiovascular disease